2021
DOI: 10.3389/fneur.2021.742365
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Neglect Subtypes, Definitions and Assessment Tools: A Scoping Review

Abstract: Objective: The objective of this scoping review was to capture the reported definitions for the subtypes of neglect post stroke and map the range of assessment tools employed for each neglect subtype.Methods: EMBASE, Emcare, Medline, and psychINFO were searched from database inception. Searching included all allied terms and mesh headings for stroke, spatial neglect, measurement, screening tools, psychometric properties. Two reviewers independently screened studies for inclusion. Primary studies with documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 119 publications
0
22
0
Order By: Relevance
“…While it is clear that neglect negatively affects activity and participation, existing clinical assessments may not be measuring neglect-related disability sufficiently. A recent scoping review of neglect measures also found that while an abundance of neglect assessments exists, the overwhelming majority are impairment-based measures that do not address participation, nor do they measure various subtypes of neglect (Williams et al, 2021). Thus, it is important that assessments that are developed address participation, IADLs, and include items that measure various neglect subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that neglect negatively affects activity and participation, existing clinical assessments may not be measuring neglect-related disability sufficiently. A recent scoping review of neglect measures also found that while an abundance of neglect assessments exists, the overwhelming majority are impairment-based measures that do not address participation, nor do they measure various subtypes of neglect (Williams et al, 2021). Thus, it is important that assessments that are developed address participation, IADLs, and include items that measure various neglect subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Such tests include cancelation tasks, visual search, copying and representational drawing (see Figure 1B ), as well as visual extinction assessment. However, no consensus exist on their efficiency to diagnose USN given the challenges in detecting and identifying underlying types of motor and visual neglect ( Williams et al, 2021 ). Numerous developments have explored the use of computerized assessment tasks (notably involving virtual reality) ( Ogourtsova et al, 2018 ) to address the limitations of existing methods ( Giannakou et al, 2022 ), such as their lack of ecological validity and inability to detect compensatory strategies ( Azouvi, 2017 ; Williams et al, 2021 ).…”
Section: Unilateral Spatial Neglect: General Scopementioning
confidence: 99%
“…6,7 Second, the language used to describe spatial neglect in the literature is complex; over 105 different terms are used, and terms such as 'neglect', 'inattention', and 'extinction' are often used interchangeably. 8 Finally, there are almost 300 published assessments of spatial neglect, most of which are specific to one or two 'sub-types' of the condition, for example, visual spatial neglect. 8 Given the time constraints of clinical practice and the complexity of assessment choice, a viable strategy is to systematically assess how spatial neglect impacts the activities of daily living of a person with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…8 Finally, there are almost 300 published assessments of spatial neglect, most of which are specific to one or two 'sub-types' of the condition, for example, visual spatial neglect. 8 Given the time constraints of clinical practice and the complexity of assessment choice, a viable strategy is to systematically assess how spatial neglect impacts the activities of daily living of a person with stroke. However, in practice, clinicians typically use informal and non-standardised observations to describe how spatial neglect impacts activities of daily living.…”
Section: Introductionmentioning
confidence: 99%